Architectural impermanence: Tectonic ecology of the Sumbanese traditional house - Gunawan, Yenny; Umbu, Justin Coupertino; Trautten, Marianne (Department of Architecture Faculty of Engineering Universitas Indonesia, 2025)
This research proposes tectonic ecology as the framework for understanding the impermanence of architecture, challenging the views of permanence in architecture and positioning impermanence as an ecological building practice. This study explores the idea of impermanence in vernacular architecture as a living spatial practice, acknowledging the growth, decay, and regeneration taking place in such a context. The research focuses on the Sumbanese traditional house in Weelewo Village, Southwest Sumba, as a case study. The Sumbanese house is constructed with natural materials and utilises joinery without using nails. The study collected data on the local construction practice through fieldwork, which included open-ended interviews, model-making demonstrations, observations, and documentations. The study reveals how local building practice understood the concept of impermanence through three interrelated principles that define the traditional house’s tectonic ecology: layered, disassembly, and regeneration. The findings demonstrate that disassembly is the mechanism of tectonic ecology, enabling the temporal transformation of materials and sustaining buildings' capacity for regeneration. The exploration of tectonic ecology contributes by offering a framework of materiality and building practices that value impermanence. In doing so, such architectural practices emphasise the rhythm of the environment, as rooted within the wider ecosystem.